(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article examines the effectiveness of games in English language learning and focuses on its impact on student motivation, engagement, and academic performance. In recent years, gamification has emerged as an innovative and effective approach to foreign language teaching, particularly in English language learning, and has been shown to enhance vocabulary retention, improve grammatical accuracy, and increase engagement.[1] Drawing on theories such as self-determination theory and constructivism, the article reviews the existing literature and presents the results of recent empirical research. The study shows that, when implemented correctly, games not only transform passive learning into active exploration, but also foster long-term interest and autonomous language practice. The article concludes that when games are used effectively, English language acquisition, especially vocabulary, grammar, and reading skills, can be significantly improved